2014
DOI: 10.1007/s10067-014-2832-7
|View full text |Cite
|
Sign up to set email alerts
|

Work disability is related to the presence of arthritis and not to a specific diagnosis. Results from a large early arthritis cohort in Argentina

Abstract: 1. Work disability is higher in patients with inflammatory arthritis as compared to the general population. 2. Prevalence of work disability is comparable among patients with undifferentiated and rheumatoid arthritis. 3. Disease activity is the main disease variable associated with work disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…There is a broad range of studies regarding work disability and unemployment; however, it must be considered that these outcomes were assessed in different ways and definitions vary among studies, causing difficultly in accurately comparing study results. In the present study, not being gainfully employed is defined as not having a paid job at time of study inclusion, whether associated with RA or not; however, in a previous study, unemployment was equated with work disability [ 37 ]. In our RA outpatient population, we found that 41% were not gainfully employed and that employment status was not related to disease duration.…”
Section: Discussionmentioning
confidence: 99%
“…There is a broad range of studies regarding work disability and unemployment; however, it must be considered that these outcomes were assessed in different ways and definitions vary among studies, causing difficultly in accurately comparing study results. In the present study, not being gainfully employed is defined as not having a paid job at time of study inclusion, whether associated with RA or not; however, in a previous study, unemployment was equated with work disability [ 37 ]. In our RA outpatient population, we found that 41% were not gainfully employed and that employment status was not related to disease duration.…”
Section: Discussionmentioning
confidence: 99%
“…It might be estimated that job offers good social status and earnings and could be important for social maintenance. Study done by found that jobless patients had elevated DAS28 (Citera et al, 2014).…”
Section: Figure 1: Means Of Quality Of Life Domainsmentioning
confidence: 96%
“…[4] RA has a profound impact on participation, from daily life activities, to, for example, a person's working life. [5][6][7] Despite a slight decrease in work disability (permanent exclusion from work) rates over the past decade, permanent work disability still occurs frequently. [8] At-work productivity loss implies that a person is present at work, but is limited in meeting work demands.…”
Section: Introductionmentioning
confidence: 99%